The fungus Paecilomyces from Leang Pettae in Maros karst area and the suggestions for rock art preservation: Jamur Paecilomyces dari Leang Pettae di kawasan karst Maros dan saran pelestarian gambar cadasnya - R.Cecep Eka Permana; Mohammad Habibi; Edy Gunawan (Berkala Arkeologi, 2021)
This paper examines microorganisms causing damage to rock arts in Leang Pettae, Maros Karst Area, South Sulawesi. The damage is indicated by a layer of white sediment on the cave walls and rock arts. This research aims to identify the microorganisms that cause the damage and to determine the preservation strategy for the rock arts. Microorganism samples were taken from the area around the damaged hand stencils and figurative paintings of babirusa (Babyrousa). The samples were cultured on PDA (Potatoes Dextrose Agar) medium at the Biology Laboratory of the Agency for Borobudur Conservation. The analysis identifies fungus from the genus Paecilomyces, which thrives in humid and wet conditions, and produces protease enzymes that affect the organic elements of the rock arts. To preserve the rock arts in Leang Pettae, it is suggested to control temperature and humidity, prevent air pollution, and limit human activities inside the cave.